2017
DOI: 10.1186/s12944-017-0488-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of inherited susceptibility to hypercholesterolemia – a comprehensive literature review

Abstract: Hypercholesterolemia is a strong determinant of mortality and morbidity associated with cardiovascular diseases and a major contributor to the global disease burden. Mutations in four genes (LDLR, APOB, PCSK9 and LDLRAP1) account for the majority of cases with familial hypercholesterolemia. However, a substantial proportion of adults with hypercholesterolemia do not have a mutation in any of these four genes. This indicates the probability of having other genes with a causative or contributory role in the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 255 publications
(434 reference statements)
5
77
0
5
Order By: Relevance
“…Some support for this may come from studies that have shown an association between mutations in APOA5 and APOC2 and hypercholesterolemia. 28 Environmental, or gene-environment interactions, may also be playing a role. Interestingly apo B levels were not significantly different between the 2 groups, although specific B-100 and B-48 assays were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Some support for this may come from studies that have shown an association between mutations in APOA5 and APOC2 and hypercholesterolemia. 28 Environmental, or gene-environment interactions, may also be playing a role. Interestingly apo B levels were not significantly different between the 2 groups, although specific B-100 and B-48 assays were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Though our patients had negative gene panel testing for many of the genes known to be associated with Mendelian hypercholesterolemia syndromes, these panels do not account for all modifier genes within this pathway nor for noncoding variants, alleles of small effect size, or polymorphisms in known genes [5,25]. Importantly, common polymorphisms in all of these cholesterol metabolism genes are associated with population-based variation in lipoprotein profile and atherosclerotic cardiovascular disease risk, and individuals with LALD are not exempt from the effects of these variants [26][27][28]. Interestingly, ezetimibe, a pharmacological inhibitor of the NPC1L1 cholesterol transporter, has shown significant benefit in both animal models and patients with LALD, consistent with noncanonical LDL pathways modifying the LALD dyslipidemia phenotype [11,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Влияние на кальций-опосредованный сигналинг обусловливает изменения уровня кальция в ýндоплазматической сети. Повышенное содержание Ca 2+ может вызывать синаптический дефицит и способствовать накоплению амилоидных бляшек при болезни Альцгеймера [16].…”
Section: функции ассоциированные с обоими заболеваниямиunclassified